Multistakeholder partnerships with the Democratic Peoples' Republic of Korea to improve childhood immunisation: A perspective from global health equity and political determinants of health equity. Issue 8 (9th June 2016) - Kim, Hani; Marks, Florian; Novakovic, Uros; Hotez, Peter J.; Black, Robert E.
Abstract: Objective: To examine the current partnerships to improve the childhood immunisation programme in the Democratic Peoples' Republic of Korea (DPRK) in the context of the political determinants of health equity. Methods: A literature search was conducted to identify public health collaborations with the DPRK government. Based on the amount of publicly accessible data and a shared approach in health system strengthening among the partners in immunisation programmes, the search focused on these partnerships. Results: The efforts by WHO, UNICEF, GAVI and IVI with the DPRK government improved the delivery of childhood vaccines (e.g. pentavalent vaccines, inactivated polio vaccine, two‐dose measles vaccine and Japanese encephalitis vaccine) and strengthened the DPRK health system by equipping health centres, and training all levels of public health personnel for VPD surveillance and immunisation service delivery. Conclusion: The VPD‐focused programmatic activities in the DPRK have improved the delivery of childhood immunisation and have created dialogue and contact with the people of the DPRK. These efforts are likely to ameliorate the political isolation of the people of the DPRK and potentially improve global health equity.